Moderation Based Al-Qur'an Education Park Curriculum at TPA Lampung Al-Qur'an Center - Rifkah Dewi; Sigit Wibowo; Herawati (al-Afkar, Journal For Islamic Studies, 2023)
The government is currently intensively introducing the issue of moderation to all elements of the state in Indonesia to be internalized by the Indonesian people. Terrorism and liberalism are considered as the impact of an immoderate understanding of religion, therefore an appropriate method is needed to internalize the values of moderation from an early age, because early age is the right time to build one's character. The purpose of this study is to examine and present the implementation of the Al-Qur'an Education Park curriculum based on moderation. The method in this research is literature study and field study with content analysis. Al-Qur'an Education Parks are required to be able to instill the values of moderation, namely tawasuth, tawazun, i'tidal, tasamuh and al-musawah through the learning process at the TPA. The inculcation of moderation values is practically derived from the four components of the curriculum, namely objectives, content, methods and evaluation. The four components must always synergize in its implementation. In its implementation, it shows that the inculcation of moderation values in the TPA curriculum contributes to forming a moderate TPA environment.